2012
DOI: 10.1111/j.1423-0410.2012.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multicomponent apheresis on donors’ haematological and coagulation parameters, iron storage and platelet function

Abstract: Background and Objectives  Multicomponent collection (MCC) enables production and processing of various blood components during one apheresis session. In this prospective crossover study, the effects of donating platelets (PLTs) and packed red blood cells (PRBCs) on donor’s blood cell count, coagulation, PLT function and iron state were analysed. Materials and Methods  Forty‐eight MCCs were performed using two different cell separators (Fenwal Amicus®, CaridianBCT Trima Accel®). Two units of platelet concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This could not be related to levels of fibrinogen or antithrombin III, which did not change significantly. Post‐multicomponent apheresis, lower clot strength (~5%) was observed, the net result of lower PLT count (~30%) and fibrinogen levels (~16%) and lower haematocrit (~9%) . Post‐RBC apheresis, again a small hypercoagulable shift was detected.…”
Section: Healthy Volunteers and Blood Donorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This could not be related to levels of fibrinogen or antithrombin III, which did not change significantly. Post‐multicomponent apheresis, lower clot strength (~5%) was observed, the net result of lower PLT count (~30%) and fibrinogen levels (~16%) and lower haematocrit (~9%) . Post‐RBC apheresis, again a small hypercoagulable shift was detected.…”
Section: Healthy Volunteers and Blood Donorsmentioning
confidence: 95%
“…A systematic review describes eight studies, but only studies were included which combined thromboelastography measurements with at least one conventional parameter of haemostasis. For the current review, only studies were included that have used citrate as anticoagulant .…”
Section: Healthy Volunteers and Blood Donorsmentioning
confidence: 99%
“…Regarding post-procedure changes in Hb, Macher et al [15] using Amicus and Trima Accel V5.2 to collect single RBC units with PLT units, showed changes very similar to those shown here, a 9% average decrease in donor Hb post-procedure which was unchanged 14 days later but returned to within 3% of the pre-procedure level within 6 weeks.…”
Section: Discussionmentioning
confidence: 70%
“…Refs. [2,13,16,20,[24][25][26]29] A funnel plot was used to rule out publication bias, which did not observe the statistically significant publication bias. The p value for hemoglobin was 0.57 and 0.47 for hematocrit, and the p value for erythrocyte count was found to be 0.09, which showed that there was no publication bias (Figures 5-7).…”
Section: Resultsmentioning
confidence: 99%